2019
DOI: 10.1021/acs.est.9b03053
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Gas and Particulate Phase Organic Emissions (C9–C37) from a Diesel Engine and the Effect of Abatement Devices

Abstract: Particulate and vapour phase emissions in the diluted exhaust of a light duty diesel engine designed for Euro 5 application have been sampled. The engine was operated in three modes, and samples were collected from exhaust without aftertreatment but also with aftertreatment by an exhaust oxidation catalyst and particle filter. The samples were analysed by 2-dimensional gas chromatography with Time-of-Flight mass spectral detection. The results show overall removal efficiencies for organic compound mass by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 52 publications
(157 reference statements)
1
18
0
Order By: Relevance
“…The carbon distribution of I/SVOCs in Figure is in broad agreement with the carbon distribution of diesel fuel reported by Gentner et al (2012), who demonstrated a sharp peak at around C10 to C13 and a broader peak at around C16-C20. A correlation analysis was carried out between the I/SVOCs measured in the London air and diluted emissions from a light-duty diesel engine designed to a Euro 5 standard under three different operation modes (low-speed/low-load, high-speed/low-load and high-speed/high load), without or with aftertreatment by a diesel oxidation catalyst (DOC) and diesel particulate filter (DPF) (Alam et al, 2019). Total I/SVOCs (sum of acyclic alkanes, cyclic alkanes and aromatics in the gas phase and particle phase) ranging from C13 to C36 collected at MR and RU correlated strongly with the diesel exhaust (Table S3), indicating that the I/SVOCs measured in London air have a similar carbon distribution and composition as those measured in the diesel exhaust.…”
Section: Chemical Composition and Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…The carbon distribution of I/SVOCs in Figure is in broad agreement with the carbon distribution of diesel fuel reported by Gentner et al (2012), who demonstrated a sharp peak at around C10 to C13 and a broader peak at around C16-C20. A correlation analysis was carried out between the I/SVOCs measured in the London air and diluted emissions from a light-duty diesel engine designed to a Euro 5 standard under three different operation modes (low-speed/low-load, high-speed/low-load and high-speed/high load), without or with aftertreatment by a diesel oxidation catalyst (DOC) and diesel particulate filter (DPF) (Alam et al, 2019). Total I/SVOCs (sum of acyclic alkanes, cyclic alkanes and aromatics in the gas phase and particle phase) ranging from C13 to C36 collected at MR and RU correlated strongly with the diesel exhaust (Table S3), indicating that the I/SVOCs measured in London air have a similar carbon distribution and composition as those measured in the diesel exhaust.…”
Section: Chemical Composition and Distributionmentioning
confidence: 99%
“…The I/SVOCs at the roadside site MR (r 2 =0.71-0.81) generally correlated better with the diesel exhaust than those sampled at the background site RU (r 2 =0.56-0.76). The on-road lightduty diesel fleet includes older vehicles without abatement devices, vehicles with only DOC, and vehicles with both a DOC and DPF (Alam et al, 2019). The correlation between I/SVOCs in London air and diesel exhaust emitted under different operation conditions without or with aftertreatment varies little.…”
Section: Chemical Composition and Distributionmentioning
confidence: 99%
“…The engine-aftertreatment system also influences IVOC emissions (Drozd et al, 2019;Alam et al, 2019;Zhao et al, 2018;Saliba et al, 2017). In order to investigate the efficiency of after-treatment system, we normalized the IVOC distributions of the https://doi.org/10.5194/acp-2020-976 Preprint.…”
Section: High Emission Factors and Distinct Volatility Distributions mentioning
confidence: 99%
“…chromatography time-of-flight mass spectrometry (GC×GC-ToF-MS). Details of this GC×GC-ToF-MS characterisation method are provided byAlam et al (2019). Briefly, the PTFE filters were spiked with internal standards and subsequently were immersed in dichloromethane (DCM) and then the mixture was ultrasonicated for 20 minutes at 20°C.…”
mentioning
confidence: 99%
“…All the analysis include consideration of internal standards and subtraction of the I+SVOC content found on the blank filters. Solvent blank injections and blank filter extractions both did not show any peaks in the chromatography and so all compounds are below the detection limit, indicating no instrument artefacts (please refer toAlam et al (2019) for more information). Data were processed and post-processed via GC Image v2.5 from Zoex Corporation.…”
mentioning
confidence: 99%